Market segmentation: venezuelan adrs (2012)
The control on foreign exchange imposed by Venezuela in 2003 constitute a natural experiment that allows researchers to observe the effects of exchange controls on stock market segmentation. This paper provides empirical evidence that although the Venezuelan capital market as a whole was highly segmented before the controls were imposed, the shares in the firm CANTV were, through their American Depositary Receipts (ADRs), partially integrated with the global market. Following the imposition of the exchange controls this integration was lost. Research also documents the spectacular and apparently contradictory rise experienced by the Caracas Stock Exchange during the serious economic crisis of 2003. It is argued that, as it happened in Argentina in 2002, the rise in share prices occurred because the depreciation of the Bolívar in the parallel currency market increased the local price of the stocks that had associated ADRs, which were negotiated in dollars.